Multifunctional Drug Delivery System: Nanosponges - Barik, Piyali; Bhaisal, Pooja Rani; Singh, Sonia (Recent Patents on Nanotechnology, 2025)
In recent years, nanotechnology has been the focus of study for the cure of different diseases, among which nanosponge delivery system is one of a kind. Nano sponges are tiny, highly porous, three-dimensional nanostructures with a size range of 250 nm-1 µm in an amorphous or crystalline structure. Nanosponges usually act as an excipient or carrier of a drug in the different delivery systems. The type of polymers and cross-linkers, along with their concentration ratio, causes variation in nanosponges's dimension and encapsulation efficiency. Nanosponges have gained prominence in recent times due to their distinct ability to encapsulate both hydrophilic and lipophilic drugs within their internal cavity, thereby improving the solubility of drugs that have low water solubility. Virus-like size helps the nanosponges to circulate within the body without getting eliminated by the immune system until they stick to the targeted part of the body, which makes it the perfect candidate for a targeted drug delivery system and controlled delivery system as well because of its slow drug release property for a more extended period. Cyclodextrin-based nanosponges are the best choice for anticancer drug delivery as their small virus-like diameter helps them in passive targeting by enhancing the enhanced permeability and retention effect, allowing the anticancer drug to stay inside the tumour cell to show more significant therapeutic action on cancer, while for active targeting to the cancerous cell, nanosponges are attached with a ligand on it for receptor binding purpose. It can be used for drug delivery in many major diseases like brain-related diseases, diabetes, cancer, fungal, hypertension, etc., in different dosage forms, like oral, topical, hydrogel, parenteral, etc. and also provide valuable information of this novel drug delivery system in the field of patent area.
Keywords: targeted drug delivery system